Plant and Marine-Derived Natural Product Research in Drug Discovery: Strengths and Perspective - Duarte, Noelia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
For centuries, nature has been an inspirational source for the discovery of drugs used in modern medicine. Nowadays, natural-based treatments continue to be employed for primary health care, particularly playing a significant role in folk medicine. In addition, we are currently observing an increasing use of natural-products-based supplements from botanical and marine sources, making their standardization and scientific validation a priority to guarantee the safety of these products. Natural products and/or synthetic derivatives using their novel structures have also been of utmost importance in drug discovery and development in several clinical areas. After a period of discreditation and reduced investment, we are now witnessing a renewed interest from the pharmaceutical industry and scientific community due to the urgent need to develop new drugs. This reprint comprises 11 original and 6 review articles dedicated to plant and marine natural products research, contributing to the scientific validation of their use and opening new perspectives in drug discovery